THE USE OF BUDIKASTA MEDIA – THE DIGITAL BOOK OF KAK ARIN THE STORYTELLER TO FORM THE ELEMENTARY STUDENTS’ NOBLE CHARACTER - Dita Rahayu; Audy Yolanda Fajri; Dini Handayani; Ani Nur Aeni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The moral education of elementary students still have lack concern because the learning process requires material guidance with well planning and assistance from other aspects, such as learning media, so that it can influence the moral development of students who deviate from state rules and regulations. Therefore, researchers utilize learning media in the form of digital books. The purpose of the research is to form the noble character of elementary students by applying innovative media. The media developed by researchers is called Budikasta (Digital Book of Kak Arin the Storyteller), this digital book discusses the brotherhood that occurs between the Muhajirin and the Ansar. The research uses the Design and Development (D&D) method with a research model retrieved by Peffers et al, there are six stages of D&D research, namely 1) identifying the problem, 2) describing the objectives, 3) designing and developing the product, 4) testing the product, 5) evaluating the testing result, and 6) confirming the testing results. The research results imply that the Budikasta learning media (Digital Book of Kak Arin the Storyteller) are suitable to use in PAI learning subjects in elementary schools.